Biological activity of lectin-like proteins in generative organs of homo- and heterostyled species of genus Linum L. - Левчук, А. М.; Лях, В. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The level of biological activity of lectin-like proteins (LLP) in the generative organs of three homostyly and three heterostyly speceis of flax were investigated. The differences in the level of lectin activity and carbohydrate specificity between homo- and heterostyly species, as well as long- and shot-styly flowers in heterostyly species were founded. It was established that in the generative organs of homostyly species compared with heterostyly species less active LLP were presented. It was shown that long-styly flowers are characterized by a high level of lectin activity compared with shot-styly flowers. It was revealed that the anther and stigma LLP were  the most active and ovary LLP – the least active. It was found that the different parts of the LLP in generative organs of same species had the identical carbohydrate specificity. All LLP were mannozospecific and proteins of homostyly species and shot-styly flowers of heterostyly species were able still recognize to galactose.